Outcomes Comparison for Microsurgical Breast Reconstruction in Specialty Surgery Hospitals Versus Tertiary Care Facilities. Issue 10 (October 2017) - Vemula, Rahul; Bartow, Matthew J.; Freeman, Matt; Callaghan, Cameron; Matatov, Tim; Jansen, David; Allen, Bob; Hilaire, Hugo St.; Tessler, Oren
Abstract : Background: Postoperative monitoring is crucial in the care of free flap breast reconstruction patients. Tertiary care facilities (TCFs) provide postoperative monitoring in an ICU after surgery. Specialty surgery hospitals (SSHs) do not have ICUs, but these facilities perform free flap breast reconstruction as well. Are outcomes comparable between the 2 facilities in terms of flap reexploration times and overall success? Methods: Retrospective study including 163 SSH and 157 TCF patients. Primary predictor was facility in which the procedure was performed. Secondary predictors included operative, demographic, and comorbidity data. Primary outcomes were flap take back rate and flap failures. Secondary outcomes were total time from adverse event noticed in the flap to returning to the operating room (OR) and total time from decision made to return to the OR to returning to the OR (decision made). Tertiary outcomes were length of stay, operative times, and blood loss. Results: Patients at the TCF were generally less healthy than SSH patients. Salvage rates and failure rates were similar between the 2 institutions. Adverse event noticed and decision made times did not differ between the 2 facilities. Overall flap success rate was 98.22% at SSH and 98.81% at TCF. No primary or secondary predictors had a significant correlation with increased odds for flap failure. Conclusion: SSHs can offer similar outcomes in free flap breast reconstruction with just as effective clinical response times to endangered flaps as found in a TCF. However, surgery at an SSH may best be reserved for healthier patients.